MARKETING STRATEGY OF SUPER LEDRE AS A TRADITIONAL SNACK AND SOUVENIR OF BOJONEGORO REGENCY: CASE STUDY OF LEDRE SUPER MORO TRESNO IN PADANGAN DISTRICT, BOJONEGORO - Andriyani, Della Agfy Dwi; Mubarokah, Mubarokah; Syah, Mirza Andrian (Universitas Nusa Cendana, 2024)
Ledre Super is a brand of traditional snacks typical of Bojonegoro Regency located in Padangan District Bojonegoro. Over time, many new ledre businesses have sprung up, and in today's modern era, many modern snacks have also sprung up, which can shift public interest and consumption. This study analyze the internal and external factors and the right strategy to increase sales volume. The methods used in this research are SOAR and QSPM. The results of the research that was done using the IE matrix based on the IFE matrix were 3.184, and the EFE matrix was 3.301. The formulation of alternative strategies using the SOAR matrix results in a market development strategy, market penetration, product development, horizontal integration, and backward integration, while the priority strategy is horizontal. Keywords: Marketing Strategy; Traditional Snacks; Ledre